2020
DOI: 10.3389/fmicb.2020.589898
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Lipid:Protein Ratio and n-3 Long-Chain Polyunsaturated Fatty Acids Alters the Gut Microbiome of Atlantic Salmon Under Hypoxic and Normoxic Conditions

Abstract: Researchers have adjusted dietary lipid:protein ratios and n-3 long-chain polyunsaturated fatty acids (LC-PUFA) to optimize the growth performance of Atlantic salmon. However, dietary impacts on the gut microbiome are lacking, especially under varying environmental conditions. To examine this response, post-smolt salmon (184 ± 5 g) were fed diets with lipid:protein ratios considered low (180, 570 g/kg) and high (230, 460 g/kg) along with low and high levels of n-3 LC-PUFA (7 or 14 g/kg) while fish were reared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 55 publications
5
41
0
Order By: Relevance
“…The lipid fraction of BSF larvae was rich with medium chain lauric acid (40% of total FAs), and contained negligible level of long-chain polyunsaturated omega-3 FAs (Additional file 2 : Table S2). This FA composition of BSF can also be responsible partially for increased LAB abundance as shown by Rimoldi et al [ 80 ] and Huyben et al [ 88 ], although the insect oil diet did not enrich LAB in the present study. Fish fed de-chitinized meal showed the highest abundance of Corynebacterium in gut microbiota as observed in rainbow trout fed BSF larvae or pre-pupae meal [ 27 , 29 ].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The lipid fraction of BSF larvae was rich with medium chain lauric acid (40% of total FAs), and contained negligible level of long-chain polyunsaturated omega-3 FAs (Additional file 2 : Table S2). This FA composition of BSF can also be responsible partially for increased LAB abundance as shown by Rimoldi et al [ 80 ] and Huyben et al [ 88 ], although the insect oil diet did not enrich LAB in the present study. Fish fed de-chitinized meal showed the highest abundance of Corynebacterium in gut microbiota as observed in rainbow trout fed BSF larvae or pre-pupae meal [ 27 , 29 ].…”
Section: Discussionsupporting
confidence: 60%
“…The predicted enrichment of FA synthesis in fish fed BSF lipid-rich de-chitinized meal and oil can mostly be due to the lack of omega-3 FAs in lipid fraction of BSF larvae (Additional file 2 : Table S2). Gut microbiota can compensate for low levels of omega-3 FAs in the diet by increasing the abundance of FA producing bacteria [ 88 ]. In agreement with this, Huyben et al [ 88 ] showed that low omega-3 FAs in a diet containing 23% lipid led to a predicted increase in microbial FA synthesis in salmon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rainbow trout have been found to have an increased preference and intake of diets with higher n-3 LC-PUFA (Roy et al, 2020), which may have occurred in the present study due to tendency for higher intake when fed both high n-3 and lipid diets (Table 4). In a parallel study, hypoxia had only minor effects on the gut microbiome, while high lipid and high n-3 LC-PUFA diets significantly influenced bacterial diversity and composition (Huyben et al, 2020).…”
Section: Main Effectsmentioning
confidence: 93%
“…Considering the importance of the hybrid striped bass in the aquaculture industry, the composition of its gut microbiome in healthy individuals has remained mostly unexplored. Indeed, in contrast to salmon [21][22][23][24][25], trout [26][27][28][29][30][31][32], and catfish [33][34][35][36][37][38], no published studies are currently available on hybrid striped bass or its parental strains using DNA sequencing-based methods; culture-independent approaches using high throughput Next-Generation sequencing platforms have been established as the gold standard for the analysis of microbiomes. Using a culturing approach, Aeromonas hydrophila was identified as a dominant species in the gut of striped bass [39][40][41][42] and hybrid striped bass [43].…”
Section: Introductionmentioning
confidence: 99%